Exploration of new functional endpoints in neuro-2a cells for the detection of the marine biotoxins saxitoxin, palytoxin and tetrodotoxin. Issue 1 (25th December 2015) - Nicolas, Jonathan; Bovee, Toine F.H.; Kamelia, Lenny; Rietjens, Ivonne M.C.M.; Hendriksen, Peter J.M.
Abstract: Marine neurotoxins accumulate in seafood and therewith represent a threat for consumers. At the European level, the use of in vivo bioassays is banned from 2015 onwards, except for the control of production areas. Cytotoxicity in the neuro-2a assay has been shown a promising in vitro alternative. However, given that cytotoxicity may be sensitive to confounding factors the current study investigates the suitability of functional endpoints as alternatives to cytotoxicity for the detection of marine neurotoxins. Microarray analyses were performed following exposure of neuro-2a cells to three marine neurotoxins (palytoxin (PlTx), saxitoxin (STX) and tetrodotoxin (TTX)) to identify genes up- or down-regulated that can be used as biomarkers for screening purposes. In addition to microarrays, the voltage dependent fluorescent probe bisoxonol was used to assess changes in cellular membrane potential. Biomarkers based on mRNA expression were detected for PlTx but not for STX and TTX. STX and TTX decreased the fluorescence of bisoxonol while PlTx showed no effect. When using cytotoxicity as the read out the neuro-2a assay detects these three neurotoxins at similar concentrations. Therefore it is concluded that the newly investigated endpoints in the neuro-2a assay are not preferred over cytotoxicity in a suitable broad and sensitive bioassay for the detection of marine neurotoxins in real practice. Highlights: We describe alternative endpoints in neuro-2a assay for screening marine neurotoxins. Biomarkers based on mRNA expression are provided for palytoxin. Fluorescence-based approach allows detection of saxitoxin below regulatory levels. We show that alternative endpoints are not preferred over cytotoxicity in neuro-2a assay.